Ai Fratelli Polacchi - poetyckie świadectwa pobytu Legionu Mickiewicza we Włoszech - P i e t r z a k - T h é b a u l t , Joanna (Colloquia Litteraria, 2023)
Four poems by Italian little known (or rather unknown at all) poets are published in annex to Władysław Mickiewicz’s Mémorial de la Légion Polonaise de 1848 créée en Italie par Adam Mickiewicz, Paris 1877. They have been ‘carefully’ preserved by Mickiewicz himself, despite he burnt a lot of papers before leaving for Constantinople in 1855. These poems, offered to Mickiewicz in 1848 while passing with his Legion from empoli to Milan, are average examples of the Italian patriotic poetry of the ‘second romanticism’ and three of them were translated and published in Polish as late as in 1961. It would be interesting to investigate more about how many literary testimonies of this ideological and military enterprise still remain in old prints and in manuscripts.